On Some Kinship Honorifics That Have Changed Meaning in Kazakh - Sherubay Kurmanbaiuly; Marlen Adilov; Gaukhar Alimbek (Türkiyat Mecmuası)
Words whose meaning has expanded or narrowed or whose original meaning has changed are phenomena characteristic of language. Words can have several meanings in Turkic languages, including Kazakh. A certain word may quite possibly have a figurative meaning in dialects or examples from oral literature. One example of this is the literary word täte, which is used in dialects in the derivative (as well as original) sense of the word. The word täte in literary language is used to refer to older female relatives. Its opposite meaning (i.e., father or uncle) is used in relation to men and has a dialectical character. Nevertheless, writers from southern regions of Kazakhstan continue to use this word’s dialectal meaning. In addition, such usage is observed in earlier works. For example, in a letter to Abai’s brother, Khaliolla, Abai used the word täte with the meaning of father. This article examines the reasons and bases for the uses of the word täte in the Kazakh language when addressing a man and analyzes the word’s scope and origin. The article also examines the meanings of other Kazakh kinship honorifics such as äje, äke, and apa, which have undergone more semantic changes compared to in other Turkic languages.